Exploring the relationship between firm's level cultural intelligence and supply chain issues - Nik Abdullah, Nik Ab. Halim; Don, Mohd Sobri; Yaakub, Sabariah (2013)
This paper investigates the relationship between two dimensions of firm’s level cultural intelligence (CQ) namely competitive CQ and structural CQ with five major supply chain issues, which include inventory issues, customer service issues, organisation issues, information/system issues and product flow issues. Data were collected among 60 manufacturers in three northern states of Malaysia via survey questionnaires. Results indicate significant and negative relationships between competitive CQ and customer service issues, inventory issues, information/system issues and product flow issues. The findings also indicate that structural CQ has a significant but negative relationship with customer service issues and organisational issues only.These findings indicate that firm’s level CQ is also important towards firm’s operations and the relationship between firm’s level cultural intelligence and supply chain issues which did not receive much attention before were also identified.This study provides empirical evidence on the impact of higher cultural intelligence in minimizing the supply chain issues.Managers should give more effort in enhancing cultural intelligence within their firms in order to maximize their supply chain performance.This study also fills the gap in the literature which previously concentrates more on individual cultural intelligence and its effect on firm’s performance.The directions for future research are then discussed.